Analisis Biaya Transaksi Peternak Sapi Perah : Studi Kasus pada Anggota Koperasi di Kabupaten Kuningan Jawa Barat (Analysis of Dairy Farmer’s Transactions Costs: A Case Study of Cooperative Member in Kuningan, West Java) - Cahyono - (Fakultas Peternakan, Universitas Padjadjaran, 2013)
Dairy farmers are groups of people who face problems of low levels of well-being. General school ofthought (mainstream) views the problem of poverty is caused by low productivity factor. The use of productivity approach in solving the poverty problem of dairy farmers needs to be supplemented by another approaches in terms of non-productivity factors. This non-productivity approach which is rarel yused is transaction cost approach. Starting from this, the study is carried out by transactions cost approach. This study specifically aims to analyze the structure of the cost transaction and the factors leading to the emergence of transaction costs encountered by dairy farmers members of cooperative in Kuningan West Java. Methods to determine the structure of the transaction cost is performed by analyzing farming and the factors that affect dairy farmers transaction costs were analyzed using multiple regression analysis. Analysis of the cost transaction structure showed that the dairy farmer transaction costs consist of contract cost (3.06%), welfare cost (1.51%), maintenance of livestock resources cost (56.52%), as well as milk delivery and feed or inputs search costs (38.90%). Transaction costs to revenue ratio for credit dairy farmers is 0.0279 and the ratio for independent dairy farmers is 0.0218. Meanwhile, the ratio of transaction costs to the total cost for credit dairy farmers is 0.0160 and the ratio for independent dairy farmers is 0.0146. Afterwards, based on the results of multiple regression analysis of determinants of transaction costs, independent variable of revenue and education have significant effect on the amount of transaction costs.Key words: transaction costs, dairy farmers, member of cooperative.